Solving real world security problems: hacking and protection - Leong, Angelina Man Ting (Nanyang Technological University, 2022)
The purpose of this project is to build Capture-The-Flag (CTF) challenges that are easily accessible and comprehensible by users who have little to no knowledge of basic ethical hacking. Many well-known CTFs available have their basic challenges paywalled. Therefore, this project aims to contribute by allowing more exposure of basic vulnerabilities that would be more digestible for beginners who would like to learn more about penetration testing.